Students' intention to learn data analytics using learning management systems in UAE higher education institutions: a study on the technology acceptance model / Nora Azima Noordin, Meera Ahmed Abdallah Yousif Al-Ali and Mariam Adil Hadid Obaid Alkhamisi - Nora Azima Noordin, Nora Azima Noordin; Ahmed Abdallah Yousif Al-Ali, Meera; Adil Hadid Obaid Alkhamisi, Mariam (Universiti Teknologi MARA, 2024)
This study examined the factors influencing students' intention to learn data analytics using Learning Management Systems (LMS) in the United Arab Emirates (UAE). Drawing on the Technology Acceptance Model (TAM), an online survey was distributed to students in Higher Education Institutions (HEIs) in the UAE who had studied data analytics online. The survey evaluated the students' attitudes toward e-learning, their Self-Efficacy (SE) in using e-learning systems, and their perceptions of the usefulness and ease of use of the LMS. Descriptive statistics, reliability analysis, and linear regression were used to analyze the data and test the four hypotheses. The study discovered that using LMS was widely accepted among students and increased their SE in learning data analytics. Both male and female students reported that LMS made it easier to manage their tasks and improved their practical learning assessments. The study provides recommendations for policymakers, practitioners, and researchers in HEIs to improve the use of LMS for online learning, specifically for data analytics courses.